Intervention Tales: Talk, Documents, and “Engagement” on a Wage Subsidy Project - Molina, Julian (Qualitative Sociology Review, 2018)
Drawing from ethnographic fieldwork on a wage subsidy project for NEETs in London, this article examines how talk and documents are used to make sense of caseloads and clients. The article draws attention to the way that staff account for clients through using “Intervention Tales.” The use of these tales provide insights into the routine implementation of labor market interventions. The article describes the work involved in documenting staff-client interactions and selecting which clients to put forward for “live vacancies.” The article shows how organizational documents, spreadsheets, and client registration forms are used as resources for assessing “hard to engage” clients during routine activities. In this sense, intervention tales, talk, and documents provide practical resources for organizing ordinary activities, such as segmenting client caseloads and characterizing individual clients.